Utilization of Kepok Banana Peel Flour (Musa paradisiaca formatypica) as a Feed Additive for Sangkuriang Catfish (Clarias gariepinus) Cultivation - Qulubi, M. Hadziq; Rahmawati, Suci Hardina; Mandala, Wintari (Research and Social Study Institute, 2025)
Background: Kepok banana peel (Musa paradisiaca formatypica) is one of the organic wastes that can be used as a feed additive and prebiotic for fish. Kepok banana peel has been less than optimally utilized even though the potential of banana in Lampung Province is very highAims & Methods: The purpose of this study was to analyze the growth of sangkuriang catfish (Clarias gariepinus) with the addition of kepok banana flour at specific concentrations and to analyze the quality of catfish cultivation water with the addition of banana peel flour. The research method was to make banana peel flour and then add it as a feed additive with a percentage of 2%, 4%, and 6%. The observations made were the growth of sangkuringan catfish and the quality of cultivation water by observing temperature, pH, and DO.Result: The results of this study indicate that the analysis of the growth of sangkuriang catfish with the addition of kepok banana flour showed that at a concentration of 6% addition to fish feed, it could increase the highest fish growth, which was 4.67g/weeks for 28 days. The results of the analysis of the quality of catfish cultivation water showed that the pH, DO, and water temperature in each treatment followed SNI 6484-6:2024.